2017
DOI: 10.1021/acs.jafc.7b00923
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidin Inhibits Mucin Synthesis and Viral Replication by Suppression of AP-1 and NF-κB via p38 MAPKs/JNK Signaling Pathways in Respiratory Syncytial Virus-Infected A549 Cells

Abstract: Airway epithelial cells are often infected by respiratory syncytial virus (RSV), one of the most common causes of asthma, bronchiolitis, chronic obstructive pulmonary disease, and pneumonia. During the infection process, excessive mucins instigate airway inflammation. However, the mechanism underlying RSV-induced airway hyper-responsiveness and inflammation is poorly understood. Furthermore, no reliable vaccines or drugs for antiviral therapy are available. In this study, the effect of the natural compound gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 41 publications
(58 reference statements)
3
28
0
2
Order By: Relevance
“…Although other groups have shown that SLN are capable of delivering other natural anti-oxidant compounds [ 58 ], to the best of our knowledge our study is the first to show the delivery of proanthocyanidins by SLN to airway epithelial cells and fluorochrome-containing SLN to the lungs in vivo. Only a previous paper showed that GSE, at the concentrations up to 20 µg/ml, was not cytotoxic to pulmonary A549 epithelial cells and reduced mucin transcript and protein expression as well as various signaling pathways involved in inflammation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although other groups have shown that SLN are capable of delivering other natural anti-oxidant compounds [ 58 ], to the best of our knowledge our study is the first to show the delivery of proanthocyanidins by SLN to airway epithelial cells and fluorochrome-containing SLN to the lungs in vivo. Only a previous paper showed that GSE, at the concentrations up to 20 µg/ml, was not cytotoxic to pulmonary A549 epithelial cells and reduced mucin transcript and protein expression as well as various signaling pathways involved in inflammation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown of the precise pathogenetic mechanisms of RSV that causes disease. The main clinical expression of RSV infection is excessive inflammatory and tissue damage (Lee et al, 2017;Vázquez et al, 2019). The release of pro-inflammatory cytokines usually causes excessive inflammatory response, mainly including interleukin IL-1b, IL-6, tumor necrosis factor (TNF-a) (Sun et al, 2018), and other members of the IL-1 gene family, for example, IL-18, IL-33 (Han et al, 2017;Yaneisi et al, 2019), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Via blocking NF- κ B and MAPK pathways, PCs in turn inhibit the mRNA expression of proinflammatory cytokines like TNF- α and IL-1 β as well as the inflammatory prostaglandin products of COX-2 [ 89 , 90 ]. In addition, PCs can suppress the replication of respiratory syncytial virus (RSV) by blocking RSV-induced NF- κ B, p38 MAPK/JNK, AP-1, and ERK activities [ 91 ].…”
Section: Mechanisms Against Osmentioning
confidence: 99%